Avaliação do conhecimento e do uso de suplementos alimentares e esteroides anabolizantes por usuários de academias na cidade de Lagarto-SE - Souza, Antonio Cleverton Alves de (2018)
Introduction: The use of dietary supplements (SA) and anabolic steroids (AAS) has been increasing significantly each year. The high consumption rates reflect in a billionaire market that invests more and more in marketing and creation of new products for the fitness world. However, this growth is worrisome, since the main health risks, especially the anabolic steroids, can be seen during the therapeutic session. Objectives: This study aims to evaluate the use and knowledge about dietary supplements and anabolic steroids by users of academies in the city of Lagarto-SE. Method: This work is a qualitative and quantitative cross-sectional study and the field research used to obtain the information of the users of the academies was carried out through the application of a validated and adapted questionnaire, with 17 objective and subjective questions, distributed in a sample intentional non-probabilistic and for the convenience of 100 volunteers. Results: The study consisted of 62 men (62%) and 38 women (38%), whose predominant age was 21 to 25 years (30%). The results show that 81% believe that SA or AEs can be used at certain times and 76% follow the manufacturer's recommendations; 52% received an indication of nutritionists; 57% have already used or know someone who used anabolic steroids. The most cited products were: Whey protein, BCAA, Creatine, Caffeine and Albumin and 17% have already used anabolic steroids. The main source of information was the Internet (46%); less than 50% of users were aware of the major deleterious effects of steroids. Conclusion: Therefore, the use of dietary supplements and anabolic steroids has been frequent, where a large number of users search for information on the Internet, presenting a low to reasonable level of knowledge about these products and their potential risks.